Life history, seasonal variation and production of Andesiops torrens (Lugo-Ortiz and McCafferty) and Andesiops peruvianus (Ulmer) (Ephemeroptera: Baetidae) in a headwater Patagonian stream - Epele, Luis Beltran (2011)
Life history descriptors of mayfly species are increasingly used in ecological assessment studies as indicator of environmental stress and also to evaluate the potential effects of climate change. We investigated the life history, annual production and competition of two congeneric mayflies: Andesiops torrens and Andesiops peruvianus in a Patagonian mountain headwater stream (La Hoya). From July 2004 to June 2005 a monthly sampling was conducted at riffle areas using a Surber net. Mean density of A. torrens ranged from 26 to 1080indm-2 whereas that of A. peruvianus ranged from 7 to 629indm-2. The annual production and P/B ratios of A. torrens (0.18gm-2, 3.90) and A. peruvianus (0.11gm-2, 3.35) at La Hoya stream were low, but within the expected values for cold water environments at high elevations. The two species had a similar larval life history with small larvae predominating in late summer and early autumn, middle size larvae being represented throughout winter, and mature larvae and emergence occurring in summer. As a result A. torrens and A. peruvianus showed moderately synchronized univoltine life cycles. The temporal interspecific overlap on both density and biomass was very low. This suggests that these two species of grazers reduce the competition for resources by having a marked temporal segregation.